Pengaruh PMDN Dan PMA Terhadap PDRB Di Provinsi Bali - Trisnu, Cok istri Sinta regina; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
The aim of this research is to know determine the influence of significant between Domestic Investment and Foreign Investment to Gross Domestic Product in Bali Province. This research uses time series data with the time period 1990-2012 and the data were analyzed with multiple linear regression technique and the level of efficiency were analyzed by calculating the ICOR (Incremental Capital-Output Ratio). Based on the analysis that the Domestic Investment and Foreign Investment have significant effect for simultaneous and for partial have positive effect and significant impact on the Gross Domestic Product then the level of efficiency of  the implementation of investments classified as highly efficient.
Keywords: GDP; domestic investment; foreign investment; ICOR